The polyphasic taxonomy of penicillium and talaromyces spp. isolated from the diverse Fynbos biome - Visagie, Cobus Meyer (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.